Comparison of the efficacy of face mask to endotracheal tube resuscitation in prematurely born infants. (24th May 2012) - Murthy, V; Shah, R; Fox, G; Campbell, M; Milner, A; Greenough, A
Abstract : Aims: Prematurely born infants often need respiratory support immediately after birth. International guidelines advise the initial use of a face mask to deliver positive pressure ventilation, although endotracheal intubation is an alternative approach, particularly in the very immature or asphyxiated infant. Our aim was to compare the efficacy of face mask to endotracheal tube (ETT) resuscitation given as first line procedure; outcomes were the expired tidal volume and end tidal carbon dioxide (ETCO2 ) levels before, during and after the first active inflation in infants born prematurely. Methods: Infants born at less than 29 weeks of gestation requiring resuscitation immediately at birth either by a face mask and t-piece resuscitation or via an endotracheal tube (ETT) were studied. A respiratory function monitor (NM3 respiratory profile monitor) was used to record airway pressure, flow, tidal volume and ETCO2 levels. Inflations were examined to identify the first active inflation (FB) defined as the first inflation associated with a spontaneous breath by the infant. The FB, the two passive breaths preceding (pre-FB), and first two passive breaths (post-FB) following the first active inflation in each infant were analysed. Results: Thirty five infants [median gestational age 24 (23–28) weeks and birth weight of 670 (530-1346) grams] were studied. Twenty infants were intubated with a size 2.5 endotracheal tube immediately after birth (ETT), the remaining 15 infants received face mask resuscitation (face mask). The tidal volumes and ETCO2 levels were significantly higher in infants resuscitated by ETT than face mask prior to and during the FB (table 1 ). Conclusion: Until the infant has made a spontaneous inspiratory effort during resuscitation, face mask resuscitation is less effective in achieving adequate ventilation than endotracheal intubation.